Evidence That Sedative Effects of Benzodiazepines Involve Unexpected GABA A Receptor Subtypes: Quantitative Observation Studies in Rhesus Monkeys - Duke, Angela N; Meng, Zhiqiang; Platt, Donna M; Atack, John R; Dawson, Gerard R; Reynolds, David S; Tiruveedhula, V V N Phani Babu; Li, Guanguan; Stephen, Michael Rajesh; Sieghart, Werner; Cook, James M; Rowlett, James K (The Journal of pharmacology and experimental therapeutics, 2018)
In nonhuman primates we tested a new set of behavioral categories for observable sedative effects using pediatric anesthesiology classifications as a basis. Using quantitative behavioral observation techniques in rhesus monkeys, we examined the effects of alprazolam and diazepam (nonselective benzodiazepines), zolpidem (preferential binding to 1 subunit-containing GABA receptors), HZ-166 (8-ethynyl-6-(2'-pyridine)-4 -2,5,10b-triaza-benzo[ ]azulene-3-carboxylic acid ethyl ester; functionally selective with relatively high intrinsic efficacy for 2 and 3 subunit-containing GABA receptors), MRK-696 [7-cyclobutyl-6-(2-methyl-2 -1,2,4-triazol-2-ylmethoxy)-3-(2-flurophenyl)-1,2,4-triazolo(4,3- )pyridazine; no selectivity but partial intrinsic activity], and TPA023B 6,2'-diflouro-5'-[3-(1-hydroxy-1-methylethyl)imidazo[1,2- ][1,2,4]triazin-7-yl]biphenyl-2-carbonitrile; partial intrinsic efficacy and selectivity for 2, 3, 5 subunit-containing GABA receptors]. We further examined the role of 1 subunit-containing GABA receptors in benzodiazepine-induced sedative effects by pretreating animals with the 1 subunit-preferring antagonist -carboline-3-carboxylate- -butyl ester ( CCT). Increasing doses of alprazolam and diazepam resulted in the emergence of observable ataxia, rest/sleep posture, and moderate and deep sedation. In contrast, zolpidem engendered dose-dependent observable ataxia and deep sedation but not rest/sleep posture or moderate sedation, and HZ-166 and TPA023 induced primarily rest/sleep posture. MRK-696 induced rest/sleep posture and observable ataxia. Zolpidem, but no other compounds, significantly increased tactile/oral exploration. The sedative effects engendered by alprazolam, diazepam, and zolpidem generally were attenuated by CCT pretreatments, whereas rest/sleep posture and suppression of tactile/oral exploration were insensitive to CCT administration. These data suggest that 2/3-containing GABA receptor subtypes unexpectedly may mediate a mild form of sedation (rest/sleep posture), whereas 1-containing GABA receptors may play a role in moderate/deep sedation.